THE GENETIC VARIATIONS OF INDIGENOUS BALINESE (BALI MULA) COMMUNITY AT SEMBIRAN VILLAGE USING MICROSATELITE DNA MARKERS - Dwitiari, Made Çri (Jurnal Biologi Udayana; Vol 16 No 1 (2012): Jurnal Biologi, 2013)
This study aimed to investigate the genetic variations of the indigenous Balinese ( Bali Mula ) population in Sembiran village utilizing four DNA microsatellite: D2S1338, D3S1358, D5S818 and D13S317. Amplified DNA analyzed with PCR SuperMix Kit, Invitrogen. Total alleles found in Bali Mula population at Sembiran village were 19 alleles. Genetic variations were determined using heterozygosity formulae, and the mean of heterozygosity of the four loci was 0,6145. Keywords: DNA Amplified, DNA microsatellite, heterozygosity.